- The Progress of Soviet Military & Defence Equipments in TNI Military Operations 1960-1975: Penggunaan Sistem Persenjataan Uni Soviet dalam Operasi Militer TNI 1960-1975 - Widodo, Bagus Raditya Brahma Widodo; Mukhamad Shokheh (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research explores the acquisition and strategic function of Soviet military equipment in the Indonesian Armed Forces (TNI) during the period 1960–1975. This study employs historical methods, including heuristics, source criticism interpretation, and historiography. The study draws upon primary sources such as official military documents, memoirs of key military figures, and archival reports, as well as relevant secondary literature. The findings reveal how Indonesia, in response to Cold War geopolitical dynamics and the deterioration of relations with the West, turned to the Soviet Union for large-scale military modernization. Soviet-supplied weaponry such as MiG fighter jets, Whiskey-class submarines, and SA-2 missiles significantly enhanced Indonesia’s military capacity, especially in the context of Operation Trikora and Operation Dwikora. However, the political shift post-1965 under the New Order regime led to severed ties with the Eastern Bloc, resulting in severe logistical setbacks and eventual decommissioning of Soviet weaponry. Despite this, Indonesia successfully adapted its defense strategy and conducted Operation Seroja in 1975 using restructured forces and new alliances. This study contributes to understanding the long-term impact of foreign military dependence and the evolution of Indonesia’s defense posture during a volatile geopolitical era.